The Matthean Antitheses In Relation To Their Old Testament Theses - MARCUS, Joel (Studia Universitatis Babeș-Bolyai Sacra Scripta, 2026)
A pervasive emphasis in the work of Karl-Wilhelm Niebuhr has been the relation between ancient Judaism and the New Testament. In an early treatment of the Matthean Antitheses (Matt 5:21-43), Niebuhr emphasized the consonance between the teaching of the Antitheses and Second Temple Jewish thought: the Matthean Jesus is expanding the Torah rather than replacing it. This essay applauds the anti-Marcionite and ecumenical impulse behind Niebuhr’s argument and notes a number of points of agreement with it, but presents a different interpretation of the third, fourth, and fifth Antitheses. Like many biblical writers and later Jewish exegetes, the Matthean Jesus sometimes radically revises the Torah while claiming to uphold it.